1999
DOI: 10.1074/jbc.274.1.397
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Serine Biosynthesis in Arabidopsis

Abstract: In plants, Ser is synthesized through a couple of pathways. 3-Phosphoglycerate dehydrogenase (PGDH), the first enzyme that is involved in the phosphorylated pathway of Ser biosynthesis, is responsible for the oxidation of 3-phosphoglycerate to phosphohydroxypyruvate. Here we report the first molecular cloning and characterization of PGDH from Arabidopsis thaliana. Sequence analysis of cDNA and a genomic clone revealed that the PGDH gene is composed of three exons, encoding a 623-amino acid polypeptide (66,453 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…Both Arabidopsis PGDH and PSAT are plastidic proteins, and their catalytic activities are not sensitive to Ser inhibition. The genes encoding Arabidopsis PGDH and PSAT have a common feature in their mRNA expression patterns, in which they demonstrated root-preferential expression (9,10). These results suggested that the phosphorylated pathway in plastids is regulated at the mRNA expression level, so as to ensure Ser formation in non-photosynthetic tissues, in which photorespiratory Ser biosynthesis is suppressed.…”
mentioning
confidence: 74%
“…Both Arabidopsis PGDH and PSAT are plastidic proteins, and their catalytic activities are not sensitive to Ser inhibition. The genes encoding Arabidopsis PGDH and PSAT have a common feature in their mRNA expression patterns, in which they demonstrated root-preferential expression (9,10). These results suggested that the phosphorylated pathway in plastids is regulated at the mRNA expression level, so as to ensure Ser formation in non-photosynthetic tissues, in which photorespiratory Ser biosynthesis is suppressed.…”
mentioning
confidence: 74%
“…Despite this non-conservative substitution, the secondary structures of McyI, NdaH, and PGDH did not appear to differ at this site, with each protein possessing a helix-loop-sheet composition. The fact that A. thaliana PGDH contains glycine in place of Arg 62 , as do most of the other cyanobacterial dehydrogenases, suggests that certain substitutions at this position may not be critical to activity because the A. thaliana PGDH can complement E. coli PGDH (serA) mutants (29 hypothesis. As Trp 139 also plays a key role in the cooperativity of Ser binding and inhibition, we predict that McyI is a noncooperative enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme Assay-PGDH activity was assayed as previously described with some modifications (22). Enzymatic activity of PGDH in the direction of NADH oxidation (the reverse reaction) was carried out at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…Arabidopsis plants were transformed using the floral dip method (28). Transformed plants were selected on Murashige and Skoog (MS) (29) agar media with 50 g/ml kanamycin and 25 g/ml To construct transgenic Arabidopsis plants expressing ApPGDH, which is targeted into the chloroplast, the fragment encoding a 60-amino acid transit peptide for chloroplast targeting was amplified from the Arabidopsis PGDH gene (22) by PCR using the primer set, preAtPGDH-NcoF and preAtPGDHNcoR. The amplified fragment was ligated into the NcoI site of pApPGDH-His6-SKϩ to generate the pAtTP-ApPGDH-His6-SKϩ vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation